BLOCKCHAIN AND THE EVOLUTION OF ACCOUNTING PROFESSION: SKILLS, ROLES, AND ETHICAL IMPLICATIONS - Franco Benony Limba; Shella Gilby Sapulette (CV. Adiba Aisha Amira, 2026)
The development of blockchain technology has brought significant changes to the practice and profession of accounting, particularly in terms of transparency, security, and efficiency in recording financial transactions. This study aims to analyze how blockchain influences the evolution of the accounting profession in terms of required skills, the professional role of accountants, and emerging ethical implications. The method used is a literature review, examining various scientific sources, including international journals, academic books, and research reports relevant to the topic of blockchain and accounting. The study results indicate that blockchain adoption is driving the transformation of accountants' skills from conventional to technology-based competencies, such as understanding distributed systems, data analysis, and digital-based auditing. Furthermore, the role of accountants is shifting from transaction recorders to strategic analysts and business advisors. Furthermore, blockchain implementation also raises ethical implications, such as issues of data privacy, professional responsibility, and the need for clear regulatory standards. Therefore, the accounting profession is required to proactively adapt to technological developments to maintain relevance and integrity in an increasingly digital business environment.